Evaluation of secondary prevention of noncommunicable diseases at the outpatient healthcare level in the Commonwealth of Independent States countries - M. N. Mamedov; V. A. Kutsenko; T. Z. Seisembekov; S. Kh. Mekhdiev; L. V. Yakubova; L. V. Kezhun; I. T. Murkamilov; Zh. A. Kauzbay; B. Zholdin; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To conduct a survey among doctors in 4 countries of the Commonwealth of Independent States (CIS) to assess the effectiveness of secondary prevention of noncommunicable diseases in outpatient healthcare.Material and methods. Outpatient healthcare physicians from 6 cities in 4 neighboring countries participated in the cross-sectional study. A total of 210 physicians of the internal medicine profile took part in the survey: Bishkek (Kyrgyzstan) — 42 physicians, Minsk (Belarus) — 37 physicians, Astana, Shymkent, Aktobe (Kazakhstan) — 55, 30, 10 physicians, respectively, Baku (Azerbaijan) — 36 physicians. The survey was carried out using an original questionnaire of the National Medical Research Center for Therapy and Preventive Medicine, which consisted of 11 blocks of questions. Answers in several gradations were offered for each question.Results. In 3 countries, among men who sought primary care in health care institutions, patients in the age range of 50-59 years prevailed, while in Azerbaijan, men aged 60-65 years dominated. In the CIS countries, patients most often seek medical attention at a outpatient clinic due to chronic coronary artery disease. In Azerbaijan, Kazakhstan and Belarus, the number of patients with type 2 diabetes with or without complications is >20%. Doctors in large cities of the CIS countries do not recommend non-drug treatment methods in up to 10% of cases. Subsidized pharmaceutical provision varies slightly between the analyzed cities. In Kazakhstan and Belarus, 70% of doctors note reaching 75% of the target indicators. In Kyrgyzstan and Azerbaijan, a similar level is achieved 2-3 times less often. In Kazakhstan, Belarus and Kyrgyzstan, a relatively high frequency is noted (satisfaction in 75% of cases), while Azerbaijani doctors claim that 52% are dissatisfied and 44% are partially satisfied with the interaction with specialized hospital-based doctors. In Azerbaijan and Belarus, 75% staffing of outpatient doctors in medical and preventive institutions prevails. In Kyrgyzstan, 100% staffing is detected in 84% of cases. At the same time, in Kazakhstan, 50% and 75% staffing has a comparable frequency. In these countries, a similar picture is observed in terms of provision of mid-level outpatient health workers.Conclusion. Among patients with noncommunicable diseases observed in outpatient clinics, patients with coronary heart disease and type 2 diabetes predominate. Adherence to therapy in every second case is at an insufficient level. Coverage of subsidized drugs and achievement of target levels of the main risk factors among patients is on average 60% of cases. In 3 of the 4 analyzed CIS countries, there are problems with staffing with doctors and medical staff.